El arbitraje en equidad - Becerra Toro, Rodrigo (2023)
Arbitration in equity places the arbiter in the role of judge . The arbiter’s procedural conduct is mainly investigative regarding the causes and origins of the conflictive relationship between the parties. The arbiter’s decision is discretionary, and thus permits a value judgment founded upon a rational and pondered appreciation of the facts. A decision in equity demands that the arbiter assume a role different to that of judge, characterized by the search for a solution that with upright criteria repairs and agrees w ith the state or the legal relationship existing between the parties. This article proposes to examine in greater depth the concept of arbitration in equity and to present its most relevant characteristics in order to suggest its viability and potential in light of the legal and economic conflicts that abound in our national and international reality.